HUBUNGAN DUKUNGAN TEMAN SEBAYA DENGAN KESEHATAN MENTAL REMAJA AKHIR DI ERA DIGITAL - Wulan Dari Febrianti; Erfan Ramadhani; Endang Surtiyoni (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT The transformation of social interactions in the digital era has introduced new challenges to university students' mental health, making peer support increasingly recognized as an important protective factor that warrants empirical investigation. This study aimed to examine the relationship between peer support and mental health among late adolescents enrolled in the Guidance and Counseling Study Program at PGRI University of Palembang, Class of 2024. A quantitative approach with a correlational design was employed by administering questionnaires to 60 respondents selected from a population of 135 students. The collected data were analyzed using the Pearson Product-Moment Correlation test. The analysis revealed a correlation coefficient of 0.622 with a significance value of 0.029 (p < 0.05), indicating a positive and statistically significant relationship between peer support and mental health. These findings suggest that the quality of peer support is associated with students' ability to maintain psychological well-being while coping with academic demands and the challenges of life in the digital era. This study extends empirical evidence regarding the role of peer support as a protective factor for mental health by highlighting the digital environment as an important context for understanding students' experiences. Furthermore, the findings provide a foundation for developing more adaptive guidance and counseling services through peer support-based programs to promote university students' mental health. ABSTRAK Transformasi interaksi sosial pada era digital menghadirkan tantangan baru terhadap kesehatan mental mahasiswa, sehingga dukungan teman sebaya semakin dipandang sebagai salah satu faktor protektif yang perlu dipahami secara empiris. Kajian ini difokuskan untuk menganalisis hubungan antara dukungan teman sebaya dan kesehatan mental pada remaja akhir yang sedang menempuh pendidikan di Program Studi Bimbingan dan Konseling Universitas PGRI Palembang angkatan 2024. Pendekatan kuantitatif dengan desain korelasional diterapkan melalui penyebaran angket kepada 60 responden yang dipilih dari populasi berjumlah 135 mahasiswa, kemudian dianalisis menggunakan korelasi Pearson Product Moment. Analisis menghasilkan koefisien korelasi sebesar 0,622 dengan nilai signifikansi 0,029 (p < 0,05), yang menunjukkan adanya hubungan positif dan signifikan antara dukungan teman sebaya dan kesehatan mental. Hubungan tersebut menegaskan bahwa kualitas dukungan yang diterima mahasiswa berkaitan dengan kemampuannya mempertahankan keseimbangan psikologis dalam menghadapi tuntutan akademik maupun dinamika kehidupan pada era digital. Penelitian ini memperluas bukti empiris mengenai peran dukungan teman sebaya sebagai faktor protektif kesehatan mental dengan menempatkan konteks kehidupan digital sebagai bagian penting dalam memahami pengalaman mahasiswa. Temuan ini sekaligus menjadi dasar bagi pengembangan layanan bimbingan dan konseling berbasis peer support yang lebih adaptif dalam mendukung kesehatan mental mahasiswa di lingkungan perguruan tinggi.